Criteria for Medium Segment Vertical Housing Selection: User Perspective - Kusumo Bintoro, Bambang Purwoko (International Journal of Integrated Engineering, 2019)
During this time, design of vertical housing in Jakarta is still lacking of attention to sustainable development aspects and focuses more on physical aspects and cost aspects. This can lead to sick building syndrome. In regard to sustainability construction aspects, the vertical housing design is not only considering cost but also health. This is the first stage of the study and aims to create a construct model developed using PLS-SEM, which consists of factors considered in the aspects of sustainable development. The second stage of the study will be developed after the filled-in questionnaire results are obtained and analyzed using PLS-SEM.